Theory of ground vehicles - Wong, J. Y. (Jo Yung) (John Wiley & Sons, Inc., 2022)
"Reducing greenhouse gas emissions is a central issue for curbing climate change, which is of great concern to the global community. As a significant portion of the emissions is associated with transportation, the use of the electric drive, hybrid electric drive, and fuel cell for ground vehicles, to facilitate replacing the internal combustion engine powered by fossil fuels, has received intense worldwide attention. To enhance safety, traffic flow, and operational efficiency of road transport, automated driving systems and cooperative driving automation have been under active development. With the growing interest shown by an increasing number of countries in the exploration of extraterrestrial bodies, such as the Moon, Mars, and beyond, research on the mobility of rovers for extraterrestrial surface exploration has attracted considerable interest. Studies of the application of terramechanics to modeling and evaluating rover mobility have been intensified. The discussions of these and other topics of current and future interest in ground vehicle technologies are included in this edition. While in this edition new topics are introduced and discussions of certain topics covered in previous editions are expanded, emphasis continues being placed on elucidating the physical nature and the mechanics of ground vehicle-environment interactions as in previous editions. Features of this edition are highlighted below. In Chapter 1, definitions of tire slip associated with the application of a driving torque and of tire skid associated with a braking torque are reviewed and updated. Identifications of tire design features, such as load carrying capacity, operating speed range, quality (treadwear), and traction, are included. Discussions of tire/road noise are expanded. In Chapter 2, a method for characterizing terrain behavior pertinent to vehicle mobility using the Bekker-Wong terrain parameters is presented. Comparisons of physics-based models with empirically based models for predicting the cross-country performance of off-road vehicles are presented. Approaches to the development of next-generation mobility models are indicated. Discussions on the physical nature of slip sinkage which may lead to vehicle immobilization on weak terrain as well as soft regolith on extraterrestrial surfaces, and methods for characterizing the relationship between sinkage and slip are included. Applications of terramechanics to the study of extraterrestrial rover mobility are outlined. Methods for predicting the performance of the rover and/or its running gear on extraterrestrial surfaces based on test data obtained on earth under earth gravity are explored. Applications of the discrete element method to the study of vehicle-terrain interaction are updated. In Chapter 3, discussions of using the electric drive, hybrid electric drive, and fuel cell to eliminate or reduce greenhouse gas emissions are expanded. Various configurations for the hybrid electric drive are evaluated. Energy consumption characteristics of battery electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and fuel cell vehicles are presented. To provide a common basis for comparing the performance characteristics of internal combustion engines, methods for converting engine power measured under test atmospheric conditions to that under reference atmospheric conditions are updated. Comparisons of fuel consumption characteristics of passenger vehicles with all-wheel drive and that with two-wheel drive, as well as comparisons of vehicles with automatic transmissions and that with manual transmissions, based on test data are also included. In Chapter 4, discussions on the necessary and sufficient conditions for achieving the optimal tractive efficiency of all-wheel drive off-road vehicles are further elucidated. In Chapter 5, the automated driving system and cooperative driving automation are introduced. The classification of the levels of driving automation and the associated enabling technologies are outlined. In Chapter 7, the evaluation of human exposure to whole-body vibration, in accordance with ISO 2631-1, Amendment 1:2010, is updated. The characterization of vertical road surface profiles by displacement power spectral density for vehicle ride assessment, in accordance with ISO 8608:2016, is presented. The use of the International Roughness Index for classifying longitudinal profile of traveled surfaces is introduced. While commercial services with passenger-carrying air cushion vehicles across stretches of water have declined since the early 2000s, the air cushion vehicle still plays an active role in defence and coast guard operations, in search and rescue missions, and in recreational activities, because of its unique capability of being able to travel across a variety of surfaces. Consequently, Chapter 8 on the introduction to air cushion vehicles is retained in this edition"--